Money Gone Up in Smoke: The Tobacco Use and Malnutrition Nexus in Bangladesh - Muhammad Jami Husain (Ubiquity Press, 2017)
Background The tobacco epidemic in Bangladesh is pervasive. Expenditures on tobacco may reduce money available for food in a country with a high malnutrition rate. Objectives The aims of the study are to quantify the opportunity costs of tobacco expenditure in terms of nutrition (ie, food energy) forgone and the potential improvements in the household level food-energy status if the money spent on tobacco were diverted for food consumption. Method We analyzed data from the 2010 Bangladesh Household Income and Expenditure Survey, a nationally representative survey conducted among 12,240 households. We present 2 analytical scenarios: (1) the lower-bound gain scenario entailing money spent on tobacco partially diverted to acquiring food according to households' food consumption share in total expenditures; and (2) the upper-bound gain scenario entailing money spent on tobacco diverted to acquiring food only. Age- and gender-based energy norms were used to identify food-energy deficient households. Data were analyzed by mutually exclusive smoking-only, smokeless-only, and dual-tobacco user households. Findings On average, a smoking-only household could gain 269-497 kilocalories (kcal) daily under the lower-bound and upper-bound scenarios, respectively. The potential energy gains for smokeless-only and dual-tobacco user households ranged from 148-268 kcal and 508-924 kcal, respectively. Under these lower- and upper-bound estimates, the percentage of smoking-only user households that are malnourished declined significantly from the baseline rate of 38% to 33% and 29%, respectively. For the smokeless-only and dual-tobacco user households, there were 2-3 and 6-9 percentage point drops in the malnutrition prevalence rates. The tobacco expenditure shift could translate to an additional 4.6-7.7 million food-energy malnourished persons meeting their caloric requirements. Conclusions The findings suggest that tobacco use reduction could facilitate concomitant improvements in population-level nutrition status and may inform the development and refinement of tobacco prevention and control efforts in Bangladesh.